Workshop Pembejaran Matematika Realistic Mathematics Education dengan konteks budaya untuk Guru di MTs Nurul Ummah Kotagede Yogyakarta - Dyahsih Alin Sholihah; Ahmad Anis Abdulla; Muhammad Najib Mubarok; Rino Richardo; Esti Nawangsasi (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Indonesia is a country rich in culture, one of which is batik, recognized by UNESCO as an intangible cultural heritage of Indonesia. Batik is not only a visual art form but also holds significant potential as a context for teaching mathematics. Unfortunately, the integration of local culture into mathematics education has not been widely implemented. Therefore, this community service activity aims to train teachers and assist students in applying Realistic Mathematics Education (RME) based on batik culture at MTs Nurul Ummah Kotagede, Yogyakarta. The activity was carried out in three stages: preparation, implementation, and evaluation. In the preparation stage, teachers were provided with training on the theory and practice of RME, which was then applied in the classroom. The lesson focused on geometric transformations, using batik patterns as a real-world context. By linking mathematical concepts to the familiar cultural context of batik, it was hoped that students would more easily understand abstract mathematical ideas and find them more meaningful. The results of the activity showed high enthusiasm from the students and positive appreciation from the teachers toward the RME model based on culture. Students demonstrated a better understanding of mathematical concepts, as the learning process connected theoretical knowledge to real-world contexts they recognized. Additionally, teachers acknowledged that using batik culture in mathematics education made the learning experience more enjoyable and meaningful. This activity proves that integrating local culture, such as batik, into RME can increase students' interest in mathematics and help them understand abstract concepts by relating them to real-life experiences.